Design And Build Smart Remotes For Iot Based Air Conditioners - Arif Maulana; Randi Dwi W.; Doni Setiawan (Jurnal Impresi Indonesia, 2024)
Progress Internet of Things (IoT) technology has open opportunity new in development device smart and capable increase efficiency energy and provide comfort more for user. One of the potential device? For automated is cooler air conditioning (AC), considering its intensive use in consumption energy at home ladder and also building offices. However, traditional AC Still own limitations in matter accessibility distance distance and efficiency energy, which is often result in waste energy consequence lack of arrangement automatically. Therefore that, research This aiming For design and develop smart air conditioner remote prototype IoT based which can controlled from distance Far as well as set up in a way automatic based on temperature data environment. Quantitative methods used? in study This covering preparation tools, observation, consultation expert, testing tools, evaluation, and withdrawal conclusion. Testing done For evaluate functionality tools, stability IoT connections, as well as effectiveness arrangement automatic in control temperature. Research results show that IoT based remote AC system developed capable arrange temperature room in a way automatic in accordance with condition environment and reduce consumption energy compared to with manual operation . System this also works increase accessibility user through control distance far as can be accessed through application mobile. Implications from study This is development more carry on from IoT technology in management device House ladder smart and economical energy. Prototype This can become base for innovation other devices in automation House as well as contribute to global efforts in subtraction consumption energy. With more implementation? wide, expected system This can support sustainability environment through efficiency energy in various sector.